The effects of implant-macro design on stress quantity and distribution around three types of fixtures by photo-elastic analysis - Shams Ak; Eyvaz ziaee A; Esfahanizadeh G; Ghoseiri R (Tehran University of Medical Sciences, 2011)
"nBackground and Aims: Considering the great incidence of implant failures due to high stresses around implant and at bone-implant interfaces, the aim of this study was to compare the effects of three different implant-macro designs on the quantity and distribution pattern of stresses around implants."nMaterials and Methods: In this experimental in vitro study, three types of implants including Biohorizon (4×10.5 mm), Iler (4×10 mm), and Swiss Plus (4.1×10 mm) were studied by applying photo-elastic method. The implants were placed within photo-elastic models with dimensions of 50×50×10 mm. Then through open tray impressed method, crowns for each implant were constructed and cemented. Vertical and oblique loads of 100 N and 150 N were applied on the cemented crowns within polariscope machine. Then the photographs were evaluated using Isochromatic Fringe Characteristics table."nResults: Under vertical loads of 100 N and 150 N, the values for Biohorizon, Iler, Swiss Plus fixtures at the cervical region were (2.35, 3.60) N, (2.50, 3.10) N, and (1.39, 2.35) N, respectively; and in apical region the values were (1.63, 2.35) N, (1.82, 2.35) N, and (2.50, 3.10) N. Under oblique loads, the measures at the cervical region were (4.00, 5.00) N, (1.82, 5.00) N, and (5.20, 6.00) N; and in apical region were "n(1.39, 2.00) N, (4.00, 2.35) N, and (2.35, 3.00) N, respectively for mentioned implants."nConclusion: Under vertical loads, the lowest cervical stresses were observed in Swiss Plus fixture and the lowest apical stress values were recorded for Biohorizon fixture. Under oblique loads, the lowest cervical stresses were found in Iler implant and lowest apical stresses were recorded for Bohorizon.